Empagliflozin attenuates hypoxia-induced heart failure of zebrafish embryos via influencing MMP13 expression - Huttunen, Roope; Haapanen-Saaristo, Anna-Mari; Hjelt Anja; Jokilammi, Anne; Paatero, Ilkka; Järveläinen, Hannu (Elsevier BV, 2025)
Background: Today, sodium glucose co-transporter 2 (SGLT2) inhibitors are more than diabetes drugs. They are also indicated in chronic heart failure (HF) treatment in both diabetic and non-diabetic patients, independently of the ejection fraction. Multiple mechanisms have been suggested behind the cardioprotective effects of SGLT2 inhibitors. However, the underlying mechanisms still remain largely unexplored. Here, we used a zebrafish embryo model to search for new potential players whereby SGLT2 inhibitors attenuate HF.
Methods: HF in zebrafish embryos was caused exposing them to chemically induced hypoxia. As a SGLT2 inhibitor, we used empagliflozin. Its effect on hypoxia-induced HF of the embryos was evaluated using video microscopy and calculation of fractional shortening (FS) of embryos´ hearts. RT-qPCR of brain natriuretic peptide (bnp) expression was also used to examine empagliflozin´s effect on HF. Transcriptome analysis of total RNA of the embryos was performed to search for new potential mechanisms contributing to the beneficial effect of empagliflozin on HF.
Results: Empagliflozin significantly attenuated hypoxia-induced HF of zebrafish embryos as shown with improved FS of the hearts and decreased bnp expression. Transcriptome analysis revealed that the improvement of HF in response to empagliflozin was accompanied with decreased matrix metalloproteinase 13a (mmp13a) expression. Treatment of hypoxia-induced embryos with MMP13 inhibitor ameliorated the impaired heart function accordingly to the effect of empagliflozin. MMP13 inhibitor was not toxic to the embryos.
Conclusions: Our study shows that empagliflozin´s favorable effect on attenuating HF is mediated via MMP13. MMP13 provides a novel option when developing new therapeutics for HF treatment.